Proprioceptive Neuromuscular Facilitation versus Sensory Motor Training in Non-Specific Low Back Pain - Made Hendra Satria Nugraha; Ni Komang Ayu Juni Antari; Anak Ayu Nyoman Trisna Narta Dewi (Jurnal Keterapian Fisik, 2021)
Background: Non-specific low back pain is a type of pain that is located in spine area and does not radiate to the legs. Non-specific low back pain can limit daily activities and cause inability to do work. The aim of this study is to compare the effectiveness of proprioceptive neuromuscular facilitation (PNF) versus sensory motor training (SMT) in the treatment of ultrasound therapy (UST) and kinesio tape (KT) insertion in non-specific low back pain. Methods: This research is an experimental with a randomized pre-test and post-test control group design, in which the study participants were divided into two groups randomly. The control group (n = 10) is given UST+PNF+KT combination, while the treatment group (n = 10) is given UST+SMT+KT combination. Therapeutic evaluation measures include: pain scale with a numeric rating scale, range of motion with a goniometer, and lower back disability with the Indonesian Version of Oswestry Disability Index. The intervention is given 3 times per 1 week for 3 weeks. Results: The results showed improvement in pain, range of motion, and lower back disability in each group (p<0.05). However, there were no significant differences when compared between groups. Conclusion: Based on these results, it can be concluded that the UST+PNF+KT combination has the same good results as the UST+SMT+KT combination in improving pain, range of motion, and lower back disability in non-specific low back pain.